Mechanical and fire retardant behaviour of Flax/Sisal fiber hybrid composites. (2022) - Rachoti, Shivakumar; Akash; Girisha, K.G.
Abstract: Bio-fiber embedded polymers play major role in the fabrication of environmental friendly materials due to their bio-degradable in nature, meticulous strength, low density, high modulus and reduced carbon footprint on the nature. Among many fibers sisal fiber and flax fiber are gaining attention as they possess satisfactory mechanical strength, eco-friendly, abundantly available and cheaper compare to bamboo, kenaf, banana fibers etc, . Sisal and flax fiber will a play an important character to manufacture a various range of automobile products with epoxy resin. Present paper deals the tensile, flexural, compression, moisture absorption behaviour and fire retardant properties of dissimilar weight percentage of NaOH treated sisal/flax fiber incorporated composites. Composites were fabricated by compression molding technique. A 40 wt% of composites shows higher tensile, flexural and compression strength compared to other composites. Burning rate of composite samples is increased with the adding of fiber wt.%. Fractured surface of composite specimens are analysed by Scanning Electron Microscopy.